Acronitrile butadiene styrene/polycaprolactam/nano carbon black composites: Selective percolation, glass transition and temperature dependence of electrical conductivity. Issue 2 (27th October 2014) - Mondal, R.K.; Dubey, K.A.; Bhardwaj, Y.K.; Panicker, L.; Varshney, L.
Abstract : Preferential percolation is a promising strategy to develop conducting composites at lower loading of conducting filler; however, little information is available on temperature dependence of conductivity of such composites. This study reports synthesis and positive temperature coefficient (PTC) behavior of a novel multiphase polymer composite in which conducting filler preferentially percolates in a composite containing two incompatible polymers, both having glass transition in the temperature range of study. High electrical conductivity and good mechanical behavior was demonstrated by acrylonitrile butadiene styrene (ABS)/polycaprolactam (PCL)/nano carbon black (NCB) composites, which was dependent on blend composition as well as on the extent of NCB loading. PTC intensity was considerably less for ternary composites than it was for binary ABS/NCB or PCL/NCB composites. Theoretical analysis of the dispersion state of NCB in this phase separated system revealed preferential distribution of NCB at the interfacial region. PTC effect was also found to decrease significantly with increase in NCB content. ABS/PCL/NCB (1:1:2) composites showed no significant temperature dependence (zero positive coefficients) up to 413 K while ABS/NCB 30 wt% NCB composites showed highest PTC. A sudden rise was observed in the glass transition region of polymers for all composites; however, the effect was less pronounced for ternary composites. POLYM. COMPOS., 37:481–487, 2016. © 2014 Society of Plastics Engineers